Saudi Arabia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper on Saudi Arabia assesses Saudi Arabia's role in the oil market and global economy. Saudi Arabia, the world's largest producer and exporter of oil, has long played a systemically important role in the global oil market. Short-term fluctuations in Saudi Arabia's oil production have partially reflected attempts to stabilize the global oil market. Saudi Arabia has on several occasions used its systemic role to raise production to fill global demand gaps created by large supply disturbances. The authorities have made significant investments in higher education to enable productive private-sector employment for new Saudi labor force entrants.